34 Improving workflow efficiency by implementing priority indication in paging communication. (29th October 2021) - Lee, Jimin; Desai, Tejas; Horwitz, Jennifer; McLean, Connor; Nelson, Matthew; Seidman, Gillian; Buba, Melanie
Abstract: Primary Subject area: Hospital Paediatrics Background: Paging is an important method of communication in hospitals but can also interrupt clinical care unnecessarily. These interruptions decrease workflow efficiency and negatively affect patient care. Objectives: The goal of this project was to decrease clinical care interruptions from non-urgent pages to pediatric residents by implementing a priority indication system that was: (1) consistently used (90% pages with a priority level indicated); (2) clearly defined (80% concordance in the priority levels between senders and recipients); and (3) satisfying to end users (80% rating the paging system as satisfied). Design/Methods: The Plan-Do-Study-Act method of quality improvement was used. The study was conducted at an academic children's hospital, where numeric paging occurs through a switchboard operator. Three priority levels (1 being most urgent) with a respective expected callback time (5-15, 15-30, 60+ minutes) were determined through a pilot study and stakeholder consensus. A priority level was selected by the page sender and displayed beside a callback number. Process measures were indication of priority levels and concordance of priority levels between senders and recipients. Outcome measures were reduced interruptions to clinical care from non-urgent pages and user satisfaction. Balancing measures included patient safety incidents. Run charts, surveys, and page logs were used to track the impact of interventions. Results: In the first two months, 1325 out of 2208 (60%) pages had a priority level indicated. In the subsequent two months after providing feedback to users, the proportion increased to 1822 out of 2410 (76%). Subsequent bimonthly indication rates have ranged between 74% and 83%. Among pages with a priority level indicated over 16 months (n=13, 934), 26% were assigned priority 1, 62% priority 2, and 11% priority 3. There was a 74% concordance in priority levels between senders and recipients. 26% of pages were received while a resident was directly interacting with a patient. Fewer residents felt that their workflow was being frequently interrupted by non-urgent pages (from 65% to 39%). End user satisfaction improved. There were no patient safety incidents. Conclusion: Using existing infrastructure, we implemented a paging priority indication system that decreased interruptions to clinical care. Residents reported improved workflow efficiency, and end users expressed improved satisfaction with paging communication. The gap in the perception of urgency between senders and recipients will need to be further evaluated. While a priority level indication is particularly pertinent to hospitals using numeric pagers, a standardized indication of priority levels can also be beneficial in hospitals using an alternative communication system.